Evaluating Argumentation Skills: Science Literacy and Scientific Approach in Junior High School - Andriani, Nely; Supardi, Supardi; Patriot, Evelina Astra (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2025)
This research aims to enhance students' argumentation skills at the junior high school level by implementing science learning based on scientific literacy. This research uses a quasi-experimental design with a quantitative descriptive method. The instruments used were (1) an essay test with an instrument in the form of scientific argumentation description questions with as many as six items and (2) an interview with the teacher about the science learning process in the classroom. To measure students' argumentation skills refer to the Toulmin Argumentation Pattern (TAP) argumentation skills indicators. This research used a sample of one of the junior high schools in Muara Enim District. The result shows student's argumentation skills are still in level 1 with 58,1% as a weak category, level 2 with 30,95 % as a weak category, and level 3 with 10,95%. The teacher through interview sessions explains that the students' argumentation skills are lacking because they are affected by low confidence and nervousness. When learners are asked, learners give short answers which cannot provide the right sentence to explain something Learners are accustomed to using local language in expressing opinions and have not been able to express argumentation orally in the form of organized sentences. Based on these findings, further research needs to be done on the application of appropriate learning models that can train students' argumentation skills.